The Impact of Professional Competencies and Cultural Legacy on Medical Leadership Competencies with Leadership Style as a Mediating Variable - Angelina Natasya Sonda; Anderson Chua; Erwin Tenggono (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study examines the influence of professional competencies and cultural legacy on medical leadership competencies, with leadership style explicitly positioned as a mediating mechanism, within a teaching hospital context in Indonesia. A quantitative cross sectional design was applied, with survey data collected from physicians holding managerial or leadership roles at Rumah Sakit Universitas Kristen Indonesia between November 2025 and January 2026. Measurement items were adapted from established instruments and assessed using a six point Likert scale. The proposed mediation model was analyzed using PLS SEM with bootstrapping procedures. The measurement model demonstrated satisfactory convergent validity, indicated by outer loadings greater than 0.70 and average variance extracted above 0.50, as well as discriminant validity with HTMT values below 0.90. Reliability criteria were also met, with Cronbach’s alpha and composite reliability exceeding 0.70. The structural model showed strong explanatory power, with R² values of 0.774 for Leadership Style and 0.696 for Medical Leadership Competencies, alongside high predictive relevance (Q² = 0.760 and 0.619). Hypothesis testing revealed significant positive effects of professional competencies (? = 0.519, p < 0.001) and cultural legacy (? = 0.432, p < 0.001) on leadership style. Leadership style strongly predicted medical leadership competencies (? = 0.527, p < 0.001) and substantially strengthened the direct effects of professional competencies (? = 0.228, p < 0.001) and cultural legacy (? = 0.129, p = 0.008). These findings highlight the central role of leadership style in translating professional and cultural foundations into effective medical leadership.